KONSELING PENYAKIT DEGENERATIF MASYARAKAT KOTA PEKANBARU - Ferdy Firmansyah; Enda Mora; Mira Febrina; Ihsan Ikhtiarudin (Jurnal Bakti untuk Negeri, 2021)
Degenerative a disease that continues to grow and can affect a person's productivity and quality of life. Usually, people only check themselves after their symptoms, even though early detection is important. The aim of the service is to provide an overview and improve the status of the community both promotively, preventively, or curatively by providing counseling about degenerative diseases. The method used is to conduct a health examination and continued with the provision of counseling. The activity was attended by 42 people in the Car Free Day area of Pekanbaru city. The activity begins with a health check that is tailored to the symptoms felt and continues with counseling. Many factors cause degenerative diseases, such as genetics, age, physical activity, and diet. This activity can increase public insight and knowledge about degenerative diseases.